British Froebelian women from the mid-nineteenth to the twenty-first century : a community of progressive educators - Palmer, Amy; Read, Jane (London : Routledge, 2020)
British Froebelian Women from the Mid-Nineteenth to the Twenty-First Century presents a series of critical case studies of individual women who worked and advocated for the cause of Froebelian and progressive pedagogy in Britain from the mid-nineteenth century until the present day. The book presents a compelling picture of how women have contributed in powerful ways to educational life and child-centred practices. The book examines the beliefs and values of its subjects, offering crucial insights into how these women forged their professional identities and practice as new thinking about education and childhood emerged, and considers the differing forms of inspiration they drew from their connections with the Froebelian community. This book will be of great interest for postgraduate students and academics in the fields of Women's Studies, History of Education, Early Childhood Education and Early Childhood Studies.
OCLC-licensed vendor bibliographic record.
Keywords: Fröbel, Friedrich, -- 1782-1852.; Early childhood education -- Great Britain -- History; Progressive education -- Great Britain -- History; Women in education -- Great Britain -- History; EDUCATION / General